Atividade tocolítica in vitro e in vivo do extrato etanólico das folhas de Varronia dardani (Taroda) J.S. Miller (Cordiaceae) em roedores - Figueiredo, Indyra Alencar Duarte (2020)
Considering that the ethanolic extract obtained from the leaves of Varronia dardani (VD-EtOHL) had a non-selective spasmolytic effect in models of tonic and phasic smooth muscles, being more potent in rat uterus, it was decided to characterize the tocolytic mechanism of action in vitro in female rats and in vivo in female mice. For in vitro tests, after the euthanasia, the rat uterus was mounted in bath chambers for isolated organ and isometric contractions were evaluated (n = 5). For in vivo tests, female mice were used (n = 6). All experimental protocols were approved by Ethics Committee on the Use of Animals of UFPB (certificate 3864230519). It was observed that VD-EtOHL relaxed the rat uterus pre-contracted both by KCl (EC50 = 27.7 ± 3.1 μg/mL) and by oxytocin (EC50 = 33.1 ± 0.7 μg/mL), suggesting that the extract can exert its tocolytic effect through a common step between the two pathways, such as voltage-gated calcium channels (Cav). To confirm this hypothesis, cumulative curves for CaCl2 were performed in the absence (EC50 = 4.7 ± 0.2 x 10-4 M) and in the presence of VD-EtOHL, and it was observed a shift to the right of the control curve with a reduction in spasmogenic potency only at the concentration of 729 μg/mL (EC50 = 7.9 ± 1.8 x 10-3 M), suggesting that the blockade of Ca2+ influx through the CaV is not the main tocolytic mechanism of the extract. It was also observed that the potassium channels, β-adrenergic receptors, cyclooxygenase and nitric oxide pathways are not involved in the tocolytic mechanism of VD-EtOHL. The inhibition of contractile pathways can also cause relaxation of the myometrium. Thus, the participation of the RhoA/Rho kinase (ROCK) pathway in the tocolytic effect of VD-EtOHL was evaluated. It was observed that in the presence of Y-27632, a nonselective ROCK blocker, the extract relaxation control curve was shifted to the left, with an increase in relaxing potency about 2 times (EC50 = 14.5 ± 2.7 μg/mL), suggesting that VD-EtOHL negatively modulates the RhoA/ROCK pathway in its tocolytic mechanism. Calmodulin plays a key role in Ca2+ signaling and smooth muscle contraction. Thus, the participation of this protein in the tocolytic mechanism of action of VD-EtOHL was evaluated, and an increase in the relaxing potency of the extract about 17 times was observed in the presence of calmidazolium, a calmodulin blocker (EC50 = 2.0 ± 0.3 μg/mL), suggesting that the VD-EtOHL exerts its tocolytic mechanism by negatively modulating calmodulin. In the acute toxicity test, VD-EtOHL (2000 mg/kg, orally.) did not induce signs of toxicity under the experimental conditions evaluated. In the protocol that simulates primary dysmenorrhea, it was observed that the extract inhibited the abdominal contortions induced by oxytocin, with a maximum effect at the dose of 1000 mg/kg (Emax = 80.2 ± 10.1% and ED50 = 105.5 ± 14.8 mg/kg), suggesting that it has tocolytic activity in vivo in female mice. Since dysmenorrhea is related to increased production of PGF2α, it was observed that the VD-EtOHL relaxed the rat uterus pre-contracted with PGF2α (EC50 = 15.4 ± 3.5 μg/mL), suggesting that the extract can negatively modulate the signaling pathway of this contractile agonist. It can be concluded that the VD-EtOHL negatively modulates the RhoA/ROCK pathway and calmodulin in rat uterus, in addition to having an anti-dysmenorrhea effect in female mice.